Continuous Heating and Cyclic Heating for Composite Materials Containing PA2200 and Ceramic Additives (Al2O3, MgO and Nanoclay) Monitoring System - MD MERAJ DANISH, (The Nucleus, 2023)
In this harsh competition, additive manufacturing (AM) is an incredible breakthrough for aerospace, automobile and tooling industries. It can transform a computer-aided-design (CAD) into 3D component without tools or human intervention. Selective Laser Sintering (SLS) is an AM technique that utilizes high power laser to sinter tiny particles of a polymer powder into a solid object based on 3D model data. This work focuses on improving material optimization for the SLS process and establishing the best fabrication settings for developing products with superior attributes. By combining a commercially-available SLS materials like: PA2200 (polyamide) with ceramic additives (e.g., Al2O3, MgO and Nanoclay), new composite materials have been produced. It is shown that these composite materials are capable to produce sintered specimens that have superior mechanical and flammability properties than that of pure PA2200.